2017
DOI: 10.5830/cvja-2016-072
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of selected cardiometabolic risk factors among adults in urban and semi-urban hospitals in four sub-Saharan African countries

Abstract: SummaryAim:Cardiovascular diseases (CVDs) are a global challenge but the burden in sub-Saharan African (SSA) countries is less well documented than elsewhere. We aimed to describe the key cardiometabolic risk factors in four SSA countries.Methods:A cross-sectional, multi-national, hospital-based study was carried out among adults (> 35 years) across four SSA countries from 12 December 2011 to 7 February 2013. Risk factors were defined using the World Health Organisation and International Diabetes Federation gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…A study among urban and rural settlers in a Ghanaian population found an increased cardiometabolic risk factors among urban settlers due to their increased sedentary and unhealthy dietary habits [ 7 ]. In sub-Saharan Africa, hypertension followed by obesity was the commonly known cardiometabolic risk factors associated with the general adult population [ 8 ]. Obesity and overweight are associated with an increased cardiometabolic risk; however, this may vary significantly by age, dietary habits, gender, and even among participants with morbid obesity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study among urban and rural settlers in a Ghanaian population found an increased cardiometabolic risk factors among urban settlers due to their increased sedentary and unhealthy dietary habits [ 7 ]. In sub-Saharan Africa, hypertension followed by obesity was the commonly known cardiometabolic risk factors associated with the general adult population [ 8 ]. Obesity and overweight are associated with an increased cardiometabolic risk; however, this may vary significantly by age, dietary habits, gender, and even among participants with morbid obesity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reported lifestyle factors include alcohol consumption, smoking [18,19] and physical inactivity [20]. The role of genetic factors in determining BMI has also been extensively reported in the literature [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…12 This rising trend may be attributed to poor detection, treatment and control rates in addition to lifestyle changes of Africans inclusive of an increase in tobacco use, excessive alcohol consumption, obesity, lack of exercise and adoption of "Western" lifestyle and diets that are high in salt, refined sugar, unhealthy fats and oils and low fibre. 10,[13][14] Furthermore, regardless of the varied non-pharmacological and pharmacological approaches to hypertension therapy, blood pressure control rates fail to meet expected targets globally. 15 Asides several factors mentioned earlier, the association of hypertension with metabolic disorders like obesity, diabetes and dyslipidaemia may be contributory to greater difficulty in blood pressure control coupled with the fact that these metabolic disorders are individually associated with adverse cardiovascular outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…16 Opportunistic screening and awareness campaigns have been recommended by the World Heart Federation as the first line key steps in improving management and prevention of cardiovascular diseases. 14,17 The 2013-2020 World Health Organisation (WHO) global action plan targeted at the prevention and control of non-communicable diseases highlighted the importance of monitoring cardiometabolic risk profile of the population. 14,18 Systematic studies incorporating random risk profile screening programs in health care facilities in both rural and urban Nigerian communities were initiated to encourage healthier lifestyle of which the Africa and Middle East Cardiovascular Epidemiological Study (ACE) is one of such.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation